Analysis of the Characteristics of Solution Absorption Heat Storage Cycles - Chen Zehua; Wang Gang; Zhao Yonghan; Zhang Qunli (Zhileng xuebao)
Solution absorption energy storage is a new energy storage and release technology characterized by high energy storage density, low heat loss, good mobility, and long-term energy storage. Energy storage density and energy storage efficiency are the key indexes for measuring the energy storage capacity of absorption energy storage systems and the key parameters for evaluating the energy conversion efficiency of absorption energy storage systems, respectively. Based on thermodynamic principles, the energy storage characteristics and applicability of absorption energy storage systems were investigated using six types of absorption solutions under different conditions. The results show that both energy storage density and energy storage efficiency increase with an increase in heat source temperature and cooling water temperature and decrease with solution concentration. At a heat source temperature of 70-120 ℃ and condensing temperature of 24-36 ℃, NaOH-H2O has the largest energy storage density and efficiency, CaCl2-H2O has the smallest energy storage density and efficiency, and LiBr-H2O has the widest applicability of temperature range.